Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1128/aac.39.9.2019
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an efflux pump in multidrug-resistant Campylobacter jejuni

Abstract: Mechanisms of drug resistance in Campylobacter jejuni were investigated. Mutant strains 34PEF r , which was resistant to pefloxacin (128-fold increase in the MIC), and 34CTX r , which was resistant to cefotaxime (32-fold increase in the MIC) and which was derived from the susceptible parent 34 s , were obtained by serial passages on pefloxacin and cefotaxime gradient plates, respectively. Both mutants showed cross-resistance to erythromycin, chloramphenicol, tetracycline, ␤-lactams, and quinolones. While the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 35 publications
(47 reference statements)
2
53
0
2
Order By: Relevance
“…Spontaneous multiple-drug-resistant mutants of K. pneumoniae, which have increased resistance to a range of unrelated antibiotics including tetracycline, have also been described (82). Similar mutants have been found in Serratia marcescens, Enterobacter spp., and Campylobacter (39). These mutants exhibited efflux of tetracycline, similar to the E. coli Mar mutants.…”
Section: Distribution Of Other Resistance Determinantsmentioning
confidence: 80%
See 1 more Smart Citation
“…Spontaneous multiple-drug-resistant mutants of K. pneumoniae, which have increased resistance to a range of unrelated antibiotics including tetracycline, have also been described (82). Similar mutants have been found in Serratia marcescens, Enterobacter spp., and Campylobacter (39). These mutants exhibited efflux of tetracycline, similar to the E. coli Mar mutants.…”
Section: Distribution Of Other Resistance Determinantsmentioning
confidence: 80%
“…A related MexA-MexB-OprM operon has been isolated from multiple-drug-resistant Burkholderia cepacia (32), while a similar system has been identified in multiple-drug resistant Campylobacter jejuni (39). An analogous system (the mtr system) has been found in N. gonorrhoeae (161).…”
Section: Distribution Of Other Resistance Determinantsmentioning
confidence: 97%
“…Efflux pump with a broad specificity; preventing accumulation of antibiotics [25] this cat gene and Sagara et al [140] reported a link between kanamycin and chloramphenicol resistance in Campylobacter following a number of cloning experiments involving the cat and kan resistance genes of a plasmid from a multiple-antibioticresistant C. coli isolate. Kanamycin resistance in Campylobacter is more commonly associated with C. coli than with C. jejuni [140].…”
Section: Genetic Mechanisms Associatedmentioning
confidence: 99%
“…Genetic alterations in this region are often associated with high-level resistance to nalidixic acid (MIC > 64-128 µg/mL) and ciprofloxacin (MIC > 16-64 µg/mL). Similarly, resistance to fluoroquinolnes may also be associated with the activation of a multi-gene efflux pump system (see below and [25]). …”
Section: Genetic Mechanisms Associatedmentioning
confidence: 99%
“…The remaining isolates showed a spontaneous mutation at position 2268 (from T to C), which was also found in 15 Campylobacter isolates that were susceptible to erythromycin (MIC, Յ4 g/ml) ( Table 3). Other studies have demonstrated an efflux of fluoroquinolones, which also contributes to antimicrobial resistance in Campylobacter isolates (3,7). Since campylobacteriosis is transmitted primarily through food, particularly food of animal origin, the presence of antimicrobial-resistant Campylobacter in raw meat products has important public health implications.…”
mentioning
confidence: 99%